Agency-Generated Research of Consumer-Generated Content: The Risks, Best Practices, and Ethics - Dickinson, Sonia; Kerr, G. (World Advertising Research Center, 2014)
Social media enable advertising agencies to engage directly with the public by participating in—and observing—real conversations. The current study recruited a Delphi panel to explore how some of the world’s leading advertising professionals view the use of social media to test, track, and evaluate advertising campaigns and how they identify related risks and ethical considerations. The findings suggest that agencies primarily use social media as a tool for understanding consumers and igniting insight, not as a means of testing creative ideas. The authors believe this research provides an important benchmark of agency best practice in social-media research and outlines ethical implications.